Morocco : Staff Report for the 2014 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2015)
This 2014 Article IV Consultation highlights that Morocco has made important strides in maintaining macroeconomic stability in a difficult environment, but challenges remain to reduce fiscal and external vulnerabilities, strengthen growth, create jobs, and tackle poverty. Growth slowed in 2014 as a result of a contraction in agricultural activity following an exceptional 2013 crop and weak demand from Europe. However, growth is expected to rebound in 2015 to about 4.4 percent and remain robust in the medium term as external demand and domestic confidence strengthen. Executive Directors have commended the authorities for their strong policy actions, which have reduced economic vulnerabilities.